HOW DO FEE INCOME AND TRADING & INVESTMENT INCOME TRIGGER THE PERFORMANCE OF LISTED COMMERCIAL BANKS IN NIGERIA? (Journal of Global Accounting, 2025)
The study focused on understanding how the performance of commercial banks listed in Nigeria is triggered by non-interest income sources such as fee income and the trading & investment income. Specifically, the study ascertained the effect extent of fee income and the Trading and Investment Income on Return on Equity of commercial Banks in Nigeria. A total of 7 licensed listed commercial banks with international capacity was sampled over a period of 12 years ranging from 2012-2023. Data were descriptively and inferentially analysed using the panel estimated generalised least square. The findings revealed that the effect of Fee Income on Return on Equity of commercial Banks in Nigeria is positive and statistically significant (p-value = 0.0000). It was further discovered that Trading and Investment Income does significantly and positively affect the Return on Equity of commercial Banks in Nigeria (p-value = 0.00000). The study therefore concluded that the significant positive relationships found between certain non-interest income streams and financial performance, especially with Return on Equity (ROE), underscore the potential for value creation through diversified revenue strategies. It was recommended that the Executive Management and Investment Strategy Teams should expand trading and investment activities with a focus on high-growth sectors and innovative financial products. Implement robust risk management practices to safeguard investments and maximize profitability. Establish a continuous feedback loop to refine strategies based on market performance data, ensuring sustained contribution to equity growth.
Keywords: : Commercial Banks; Fee Income; Performance; Trading & Investment Income; Return on Equity